벼흰잎마름병 저항성 고품질 중생 벼 ‘해품’ - 남정권(Jeong-Kwon Nam); 박현수(Hyun-Su Park); 백만기(Man-Kee Baek); 조영찬(Young-Chan Cho); 김우재(Woo-Jae Kim); 김정주(Jeong-Ju Kim); 김보경(Bo-Kyeong Kim); 김기영(Ki-Young Kim); 신운철(Woon-Chul Shin); 고종철(Jong-Cheol Ko); 이건미(Gun-Mi Lee); 박슬기(Seul-Gi Park); et al. (Korean journal of breeding, 2019)
‘Haepum’ is a bacterial blight-resistant, medium maturing rice cultivar with high grain quality. It was derived from a cross between ‘Iksan493’ (cultivar name ‘Jinbaek’) and the F1 cross between ‘Iksan495’ (‘Dacheong’) and ‘Iksan496’ (‘Jungmo1005’). Of these three cultivars, ‘Jinbaek’ is a bacterial blight-resistant mid-late maturing rice cultivar with high grain quality, ‘Dacheong’ is a mid-late maturing rice cultivar with multiple resistance to disease and insects, and ‘Jungmo1005’ is a mid-late maturing rice cultivar with lodging tolerance. To develop fixed lines, the anther culture method was applied to F1 plants. The cultivar ‘Haepum’ was selected using the pedigree method, yield trials, and local adaptability tests. The heading date of ‘Haepum’ was August 11th, three days earlier than that of ‘Nampyeong’ cultivar. Haepum’ is a cultivar tolerant to lodging and it has short culms. Due to its low rate of viviparous germination, ‘Haepum’ could be useful for preventing pre-harvest sprouting in cultivation of medium maturing rice in the southern plain area of Korea. ‘Haepum’ carries two bacterial blight resistance genes (Xa3 and xa5), and in our study, it exhibited high-level and broad-spectrum resistance against bacterial blight, including K3a, the most virulent race in Korea. ‘Haepum’ is also resistant to the rice stripe virus and moderately resistant to rice blast. The yield of ‘Haepum’ was similar to that of ‘Nampyeong’. ‘Haepum’ showed excellent grain appearance and good taste of cooked rice, and therefore it could contribute to the development of bacterial blight-resistant rice cultivars of improved quality. ‘Haepum’ would be suitable for cultivation in the southern plain area of Korea as well as in bacterial blight-prone areas. (Registration No. 6068) KCI Citation Count: 2